2021
DOI: 10.1007/s00464-021-08647-z
|View full text |Cite
|
Sign up to set email alerts
|

Purely ropivacaine-based TEA vs single TAP block in pain management after elective laparoscopic colon surgery within an upgraded institutional ERAS program

Abstract: Background The aim of this study was to compare thoracic epidural analgesia (TEA) with transversus abdominis plane (TAP) block in post-operative pain management after laparoscopic colon surgery. Methods One hundred thirty-six patients undergoing laparoscopic colon resection randomly received either TEA or TAP with ropivacaine only. The primary endpoint was opioid requirement up to 48 h postoperatively. Intensity of pain, time to onset of bowel function, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Han et al demonstrated that TAP blocks did not show additional analgesic effects when superimposed on intrathecal morphine 75 . When compared with thoracic epidural analgesia, one study showed less early morphine consumption in the epidural than in the TAP group, 58 whereas no difference was detected in two other studies 59,60 . Hamada et al 76 showed that the addition of dextran to levobupivacaine could prolong analgesic effects of TAP blocks in a setting without adequate baseline analgesia.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Han et al demonstrated that TAP blocks did not show additional analgesic effects when superimposed on intrathecal morphine 75 . When compared with thoracic epidural analgesia, one study showed less early morphine consumption in the epidural than in the TAP group, 58 whereas no difference was detected in two other studies 59,60 . Hamada et al 76 showed that the addition of dextran to levobupivacaine could prolong analgesic effects of TAP blocks in a setting without adequate baseline analgesia.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies had more than two relevant study arms. These were separately listed for each relevant comparison, making the sum of studies in the following listing higher than the number of studies included: seven studies investigating adjuvant systemic analgesics, 39–45 three studies investigating varying degrees of neuromuscular blockade, 46–48 seven studies investigating intravenous lidocaine, 43,49–54 six studies investigating epidural analgesia, 55–60 four studies investigating spinal opioids, 55,61–63 twenty-eight studies investigating truncal nerve blocks, 53,58–60,64–87 seven studies investigating wound infiltration, 54,57,72–74,88,89 four studies investigating intraperitoneal local anaesthetics (IPLA) 90–93 and seventeen studies investigating surgical techniques 94–110 . Supplemental Table 1, http://links.lww.com/EJA/A901 lists the summary of key results from studies evaluating systemic analgesics, systemic analgesic adjuncts, regional analgesia and surgical procedures used to support the recommended interventions in patients after laparoscopic colectomy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations